Target thrust measurement for applied-field magnetoplasmadynamic thruster. (24th May 2018) - Wang, B; Yang, W; Tang, H; Li, Z; Kitaeva, A; Chen, Z; Cao, J; Herdrich, G; Zhang, K
Abstract: In this paper, we present a flat target thrust stand which is designed to measure the thrust of a steady-state applied-field magnetoplasmadynamic thruster (AF-MPDT). In our experiments we varied target-thruster distances and target size to analyze their influence on the target thrust measurement results. The obtained thrust-distance curves increase to local maximum and then decreases with the increasing distance, which means that the plume of the AF-MPDT can still accelerate outside the thruster exit. The peak positions are related to the target sizes: larger targets can make the peak positions further from the thruster and decrease the measurement errors. To further improve the reliability of measurement results, a thermal equilibrium assumption combined with Knudsen's cosine law is adapted to analyze the error caused by the back stream of plume particles. Under the assumption, the error caused by particle backflow is no more than 3.6% and the largest difference between the measured thrust and the theoretical thrust is 14%. Moreover, it was verified that target thrust measurement can disturb the working of the AF-MPD thruster, and the influence on the thrust measurement result is no more than 1% in our experiment.